Why ODL is an alternative for visually impaired learners in 21st century - Wong , Huey Siew (2019)
Open and distance learning (ODL) as “a way of providing learning opportunities that is characterised by the separation of teacher and learner in time and or place; …the use of a variety of media… [For] two-way communications that allow learners and tutors to interact; [and] the possibility of occasional face to face meetings between tutor and learners (COL’s; 2009). Today, ODL allows learners to access instruction and learning materials including those with disabilities. With regard to this new era of learning approach, it raised several significant questions as to why visually impaired learners choose to pursue their study in ODL institution, does ODL accommodate visually impaired learners’ for higher education particularly in the 21st century? This is a qualitative study which in-depth interviews being done on 10 visual impaired graduates either with low vision or totally blind who were studying in OUM, to find out why they chose ODL University to pursue their study. Besides, this study is also meant to detect what is their main difficulties and needs in the ODL environment. The finding indicated that ODL is an alternative for visually impaired to pursue their higher degree although they had face some accessibilities issues. (Abstract by author)